O Princípio do Iceberg nas telas: personagem e espaço na construção de um Hemingway ficcional - Nascimento, Simone dos Santos Machado (2018)
Ernest Hemingway is a modern American writer who has been famous for his simple, objective and carefully structured style, which sought to make the most of as little information as possible. This writing style was defined by the author as the art of omission, a particular aspect which has become known as the Iceberg principle (Baker 1974, p. 126). Thus, this doctoral dissertation investigates how the writer worked this principle in the short stories “The Killers” (1927) and “The Snows of Kilimanjaro” (1938) as well as in their respective film adaptations, namely, The Killers (1946, directed by Robert Siodmak) and The Snows of Kilimanjaro (1952, directed by Henry King). The theoretical background discussions are related to comparative literature (CARVALHAL, 1986; COUTINHO, 2011), translation studies (TOURY, 1995; BASSNETT, 2005) and film adaptation (LINS, 1984; STAM, 2006; 2009). Our main objective is to observe how such principles are developed in both the literary and filmic texts, regarding the construction of the central characters and the narrative space. The literature review we have made has shown us that the film production carried out according to the Hollywood system follows a set of recurring principles based on the first half of the twentieth century. In addition, our readings have pointed out that the filmic genres as melodrama and noir film were used to establish moral values in the American society, especially after World War II. In regard to Hemingway and his production, the bibliographic study has shown that both writer and his literary work merge in the fictionalization of personal and professional life as in the construction of his narratives. Perhaps for this reason, his production has achieved a wide and varied public, and influenced a generation of young people to adopt Hemingway’s standards and its characters in their way of life as well. The analysis of the short stories has suggested that both obey the formal criteria of the principle of Iceberg. We have further identified that the heroes of those narratives follow the code of honor established by the writer, also that the elements of space composition can reveal important information for the construction of Hemingway’s characters. The analysis of the film adaptations, on the other hand, has shown that the directors dealt with the short stories in different ways. In The Killers, we believe that Siodmak has proposed a particular principle of Iceberg for his production. The clues left in the scene, as well as the use of common features in Hemingway's work, may provide information about the characters and stimulate the viewer to a closer reading of what is on the screen. In The Snows of Kilimanjaro, King has suggested a distinct narrative and opted for a more pleasant, end and a more detailed narrative to facilitate linear reading for the public. We believe that both adaptations have proposed social applications to the public at the time as a way of spreading moral values, especially among North American people, also that a larger clipping of adaptations could reinforce or refute the idea of a Hemingway fictional identity.